Analisis Pengendalian Kualitas PT DMI Untuk Mengurangi Tingkat Kerusakan Pada Produk Servo Motor dengan Menggunakan Metode Six Sigma - Rizky Ramdani Miftahul Fadilah; Lastri Sulastri; Jimmy Alfaruqi Ramadan; Irvan Firdaus; Tri Ngudi Wiyatno (JOURNAL SAINS STUDENT RESEARCH, 2025)
The manufacturing industry, particularly in the automotive and electronic component sectors, faces various challenges in producing high-quality goods while maintaining optimal production efficiency. PT DMI, which is engaged in manufacturing automotive components, is trying to improve the quality of its products, especially on servo motor components that play an important role as drivers in various automotive applications. However, the company was experiencing serious problems related to a high rate of product defects, which resulted in additional costs due to the remanufacturing process and decreased customer satisfaction.To overcome these issues, an effective quality control approach is needed. One method that has proven effective is Six Sigma, which focuses on reducing variability in the production process and eliminating product defects. Through the DMAIC (Define, Measure, Analyze, Improve, Control) approach, Six Sigma can help companies identify and resolve the source of problems that cause product defects. This research aims to implement Six Sigma as a quality control strategy at PT DMI and evaluate its effectiveness in reducing defects in servo motor products. Thus, the company is expected to increase productivity and meet international quality standards.